Pengaruh Alternative Dispute Resolution Terhadap Pergeseran Tren Penyelesaian Sengketa Melalui Jalur Litigasi - Ahmad Zaid Al Baihaqi; Dera Marshanda; Asep Suherman (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
Business disputes often arise from differing interpretations of the parties' rights and obligations. Although Law No. 30 of 1999 regulates Alternative Dispute Resolution (ADR) as an alternative to out-of-court dispute resolution, business actors in Indonesia still tend to choose litigation due to its binding legal force and the certainty of enforceable decisions. This study aims to examine the factors inhibiting the implementation of ADR and describe the concept of "win-win" solutions that are driving the shift in business resolution trends from litigation to non-litigation mechanisms. A normative research method was used, using a regulatory and contextual approach through a study of regulatory literature and legal doctrine. The results reveal obstacles such as incomplete regulations, institutional limitations, a lack of understanding, and a strong litigation culture. However, the concept of ADR, which offers win-win solutions, is increasingly popular due to its speed, efficiency, and the maintenance of long-term business relationships.